Interweaved Si@C/CNTs&CNFs composites as anode materials for Li-ion batteries - Zhang, M.; Hou, X.; Wang, J.; Li, M.; Hu, S.; Shao, Zongping; Liu, X. (2014)
Novel silicon@ carbon/carbon nanotubes&carbon nanofibres (Si@C/CNTs&CNFs) composites have been successfully synthesized by a serious of high-energy wet ball milling, closed spray drying and subsequently chemical vapor deposition methods, in which carbon nanotubes and carbon nanofibers are interweaved with carbon coated silicon (Si@C) spherical composites. As anode materials for lithium-ion batteries, the Si@C/CNTs&CNFs composites demonstrate a high first discharge capacity and excellent cycle ability. The high initial specific discharge capacity is approximately 2169 mA h g -1 and a reversible specific capacity approached 1195 mA h g -1 after 50 cycles at a high current density of 300 mA g -1. © 2013 Elsevier B.V. All rights reserved.